The Effect of Reciprocal Teaching Learning Strategies and Academic Ability to Oral Activities and Cognitive Learning Outcomes of Biology - Aidil Adhani (Pascasarjana Universitas Negeri Malang (UM), 2014)
Pengaruh Strategi Pembelajaran Reciprocal Teaching dan Kemampuan Akademik terhadap Aktivitas Lisan dan Hasil Belajar Kognitif Biologi Abstract: The fact of the low level quality of education in Indonesia is the low cognitive learning outcome and oral activity. A strategy is needed to help students increase cognitive learning outcome as well as students’ oral activity. The use of Reciprocal Teaching therefore becomes a chance for students to develop their oral activity in order to increase the cognitive learning. Result of the research shows that (1) the learning strategy effects oral activity and the students’ cognitive learning outcome. Compared to conventional strategy, Reciprocal Teaching learning strategy potentially increases the oral activity and students’ cognitive learning outcome, (2) academic ability effects the oral activity and the students’ cognitive learning outcome, and (3) the interaction between learning strategy and academic level does not affect oral activity and students’ cognitive learning outcome.Key Words: reciprocal teaching, academic level, oral activity, cognitive learning outcome Abstrak: Fakta bahwa mutu pendidikan di Indonesia masih berada pada kategori rendah ditunjukkan rendahnya aktivitas lisan dan hasil belajar kognitif. Diperlukan suatu strategi pembelajaran yang dapat membantu siswa dalam meningkatkan aktivitas lisan siswa dan hasil belajar kognitif. Penggunaan strategi Reciprocal Teaching menjadi kesempatan bagi siswa untuk mengembangkan aktivitasnya. Hasil penelitian menyimpulkan bahwa (1) strategi pembelajaran berpengaruh terhadap aktivitas lisan dan hasil belajar kognitif siswa. Strategi pembelajaran Reciprocal Teaching berpotensi meningkatkan aktivitas lisan dan hasil belajar kognitif siswa dibandingkan dengan strategi konvensional, (2) kemampuan akademik berpengaruh terhadap aktivitas lisan dan hasil belajar kognitif siswa, dan (3) interaksi antara strategi pembelajaran dan kemampuan akademik tidak berpengaruh terhadap keterampilan aktivitas lisan dan hasil belajar kognitif siswa.Kata kunci: reciprocal teaching, kemampuan akademik, aktivitas lisan, hasil belajar kognitif